2016
DOI: 10.1155/2016/9871976
|View full text |Cite
|
Sign up to set email alerts
|

Navigated Pattern Laser System versus Single-Spot Laser System for Postoperative 360-Degree Laser Retinopexy

Abstract: Purpose. To compare three 360°-laser retinopexy (LRP) approaches (using navigated pattern laser system, single-spot slit-lamp (SL) laser delivery, and single-spot indirect ophthalmoscope (IO) laser delivery) in regard to procedure duration, procedural pain score, technical difficulties, and the ability to achieve surgical goals. Material and Methods. Eighty-six rhegmatogenous retinal detachment patients (86 eyes) were included in this prospective randomized study. The mean procedural time, procedural pain scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(29 reference statements)
1
3
0
1
Order By: Relevance
“…Furthermore, the study has shown that this laser can effectively deliver treatment quickly (median 200 s) and by a range of different laser operators. These results are comparable to previous studies using conventional laser methods [9]. In this study, the treatment was successful for 95.7% of patients with a single laser session and 100% of patients with two laser sessions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, the study has shown that this laser can effectively deliver treatment quickly (median 200 s) and by a range of different laser operators. These results are comparable to previous studies using conventional laser methods [9]. In this study, the treatment was successful for 95.7% of patients with a single laser session and 100% of patients with two laser sessions.…”
Section: Discussionsupporting
confidence: 89%
“…A second potential limitation was that this study had several different laser users. The clinical efficacy of laser is known to vary based on laser user [9]. However, we were not able to perform sub-group analysis and compare the data within the operator groups because the sample sizes and complication rates were too small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the drawbacks of intraoperative 360° laser retinopexy include increased total operating time and the need for scleral depression to coagulate peripheral retinal locations. A navigated pattern laser (Navilas) could also have been used postoperatively [ 19 ]. A higher rate of RRD recurrence was observed in eyes filled with silicone oil, but this could also be attributed to a selection bias, as silicone oil is typically used in eyes perceived to be at a higher risk of re-detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Однако опцией включения в оптическую ось дополнительных линз обладает лазерная система NAVILAS. Эта система включает сканирующий лазерный офтальмоскоп, работающий в инфракрасном и полихромном режиме, совместима с различными широкопольными контактными линзами и применяется для выполнения лазерных вмешательств как на периферии, так и в центре глазного дна [5,6]. Поскольку система разработана для использования с линзой, позволяющей визуализировать до 80° глазного дна, ее возможности при комбинации с линзами с бóльшим углом обзора не известны.…”
unclassified